Study of the Effect of Habit, Perceived Enjoyment, and Perceived Risk on Adoption and Recommendation, Mediated by Behavioral Intention on Bank Negara Indonesia Mobile Banking Application - Aditya, Aditya; Sijabat, Rosdiana (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2025)
This study aims to investigate, under behavioral intention, the link between habit, perceived enjoyment, and perceived risk on adoption and recommendation mediated. There were 255 respondents in total from a survey approach for data collection. This study gathers questions online using Google Forms from consumers using primary data. This study applies non-probability sampling as its method. Respondents for this survey have used mobile banking from Bank Negara Indonesia. The study used Smart PLS (Partial Least Square) software version 4.1.0 in a variant-based structural equation modeling method. The findings of this study reveal that habit has a significant and favorable effect on behavioral intention; perceived enjoyment has a substantial and favorable impact on behavioral intention; perceived risk has an essential and favorable effect on behavioral intention; behavioral intention has a significant and favorable impact on adoption; behavioral intention has a substantial and favorable effect on recommendation. The originality of this study is the submission of an empirical research model never done to determine the impact of the relationship between habit, perceived enjoyment, and perceived risk on adoption and recommendation mediated by behavioral intention on the Bank Negara Indonesia mobile banking application. This study is supposed to give Bank Negara Indonesia management insights on how to raise the mobile banking application user count.